Optimalisasi Foto Udara Unmanned Aerial Vehicle (UAV) Sebagai Media Pembelajaran Penginderaan Jauh - Kristhoper Simanungkalit; Muhammad Ridha Syafii Damanik; Darwin Parlaungan Lubis (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2019)
AbstractThis study aims (1) To find out how the accuracy of Unmanned Aerial Vehicle (UAV) aerial image quality using the Omission-Commission method. (2) How to use UAV aerial imagery as remote sensing learning media when viewed from the aspects of media feasibility, material worthiness, and student response. This research was conducted at the Medan State University Campus located at Jalan William Iskandar, Pasar V, Medan Estate Village, Medan North Sumatra. This location was chosen based on strategic location considerations for mapping. The results of this study indicate that the quality of the level of precision aerial photographs obtained from aerial photography results in the level of precision aerial photographs reaching above 95% with excellent categories, and aerial photographs obtained are more inclined towards omission which is influenced by the camera distortion factor , and the feasibility of UAV aerial photography learning media in terms of the aspects of the feasibility of the media achieving an assessment score of 85%, the feasibility aspects of the Material achieving an assessment score of 85% and, the results of the feasibility of instructional media based on material experts and media experts reach a score level of 85% and deserve to be used as a medium learning. The results of student responses obtained received an 89% assessment score, which results from the assessment of student responses that have been said to be good.Keywords: UAV, Remote Sensing, Unimed, Learning Media AbstrakPenelitian ini bertujuan (1) Untuk mengetahui bagaimana kualitas akurasi citra foto udara Unmanned Aerial Vehicle (UAV) dengan menggunakan metode Omisi-Komisi. (2) Bagaimana pemanfaatan citra foto udara UAV sebagai media pembelajaran penginderaan jauh bila di lihat dari aspek kelayakan media, kelayakan materi, dan respon mahasiswa. Penelitian ini dilaksanakan di Kampus Universitas Negeri Medan terletak di Jalan William Iskandar, Pasar V, Kelurahan Medan Estate, Medan Sumatera Utara. Lokasi ini dipilih atas pertimbangan lokasi yang strategis untuk melakukan pemetaan. Hasil penelitian ini menunjukkan bahwa Kualitas tingkat presisi foto udara yang didapatkan dari hasil pemotretan foto udara menghasilkan tingkat presisi foto udara mencapai diatas 95% dengan kategori sangat baik, dan foto udara yang didapatkan lebih condong ke arah omisi yang mana hal ini dipengaruhi oleh faktor distorsi kamera, dan Kelayakan media pembelajaran foto udara UAV ditinjau dari aspek kelayakan Media mencapai skor penilaian 85%, Aspek kelayakan Materi mencapai skor penilaian 85% dan, hasil dari kelayakan media pembelajaran berdasarkan ahli materi dan ahli media mencapai tingkat skor 85% dan layak dijadikan sebagai media pembelajaran. hasil respon mahasiswa yang didapatkan mendapat skor penilaian 89% yang mana hasil dari penilaian respon mahasiswa sudah dikatakan bagus.Kata Kunci: UAV, Penginderaan Jauh, Unimed, Media Pembelajaran